2018
DOI: 10.7554/elife.39658
|View full text |Cite
|
Sign up to set email alerts
|

Pericentromeric hypomethylation elicits an interferon response in an animal model of ICF syndrome

Abstract: Pericentromeric satellite repeats are enriched in 5-methylcytosine (5mC). Loss of 5mC at these sequences is common in cancer and is a hallmark of Immunodeficiency, Centromere and Facial abnormalities (ICF) syndrome. While the general importance of 5mC is well-established, the specific functions of 5mC at pericentromeres are less clear. To address this deficiency, we generated a viable animal model of pericentromeric hypomethylation through mutation of the ICF-gene ZBTB24. Deletion of zebrafish zbtb24 caused a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Specifically, we showed that ZBTB24 is a transcription factor that positively regulates CDCA7 expression by binding to and activating the CDCA7 promoter (Wu et al, ). This observation has subsequently been validated in different studies using additional cell lines (Rajshekar et al, ; Thompson et al, ), demonstrating that this regulation is highly conserved. To dissect how missense variants of ZBTB24 affect its biological function, we established two independent experimental assays that used Cdca7 promoter activity and ZBTB24 binding to the CDCA7 promoter as a readout.…”
mentioning
confidence: 66%
“…Specifically, we showed that ZBTB24 is a transcription factor that positively regulates CDCA7 expression by binding to and activating the CDCA7 promoter (Wu et al, ). This observation has subsequently been validated in different studies using additional cell lines (Rajshekar et al, ; Thompson et al, ), demonstrating that this regulation is highly conserved. To dissect how missense variants of ZBTB24 affect its biological function, we established two independent experimental assays that used Cdca7 promoter activity and ZBTB24 binding to the CDCA7 promoter as a readout.…”
mentioning
confidence: 66%
“…Although HELLS was already known to contribute to DNA methylation at murine centromeric repeats through direct interaction with DNMT3B [133,134], a role for ZBTB24 and CDCA7 in DNA methylation maintenance at murine centromeric repeats was only recently elucidated [130]. HELLS and CDCA7 act as a complex, namely CHIRRC (CDCA7-HELLS ICF-Related nucleosome Remodeling Complex), to regulate nucleosome structure, likely modulating its accessibility to DNA methyltransferase activities [135].…”
Section: Dna Methylation and Centromere Stability: Insights From Pmentioning
confidence: 99%
“…In addition, a role for ZBTB24 in the positive transcriptional regulation of CDCA7 has been demonstrated both in mouse and human [131,138,139]. Methylation reduction of the pericentromeric satellite 1 scored in a Zebrafish model of ICF 2 (ZBTB24 mutation) elicited an increased generation of satellite transcripts, which in turn activated innate immunity [134]. It will be interesting to address whether this phenomenon contributes to the clinical signs of ICF patients, or to the etiology of some autoimmune pathologies.…”
Section: Dna Methylation and Centromere Stability: Insights From Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome-wide ChIP-seq studies reported that ZBTB24 is mainly enriched at CpG-rich promoters [77,78] and that its C2H2 zinc fingers direct sequence-specific binding [78]. Down-regulation of cdca7 has also been observed in a zbtb24 knockout zebrafish model [80], demonstrating that CDCA7 is probably a highly conserved ZBTB24 target.…”
Section: Functions For Icf Genes In Dna Methylation Pathways and Beyondmentioning
confidence: 99%